The presence of spurs in the southeastern Baltic area in the Roman Iron Age and Migration Period – some remarks - Smółka, Emilia (Archaeologia Lituana, 2015)
There were two dominating cultures developing on the south-east coast of the Baltic Sea in the Roman Iron Age, namely the Wielbark and Balt cultures. The former developed as a result of the migration of Goths into territories which in the Pre-Roman Iron Age had been occupied by the Oksywie communities. The latter, on the other hand, continued traditions which had already been present in the area. Cultural transformations in Central Europe at the turn of the eras put these two populations under influence of the early Roman Iron Age stylistics of North-Central Europe (see also Wołągiewicz, 1981, p. 165). [...]